The level of phonemic persuasion in Sicilian Islamic Arabic poetry - Al-Musharraf, Khawla Jabbar Hamad; Al-Fartousi, Ahmed Abdel Hussein (Al-Adab Journal, 2022)
Phonemic persuasion is considered one of the methods used by poets in their poems. In order to create persuasion in the mind of the recipient; When in their khajjat ​​full disclosure, the poets employed the phonemic level in various aspects such as repetition, accent and others, which formed a painting that has its presence in Sicilian poetry. Sicilian poetry, which included a number of poets who had the greatest impact on the poetry of this city. The research in the field of phonological lesson requires us to delve into the midst of Sicilian poetry, which carried the climate of diversity. As a result of the conditions that surrounded it in terms of climate and nature, as well as the multiplicity of its rulers and the ages that it went through, in addition to that, the phonemic level carries many dimensions, deep in terms of objective diversity, and the overlap between its data that appear among the poets, especially the employment of repetition, or the nature of the tone, or The characteristics of intonation, or even sounds in terms of loud and whisper, and other phonemic aspects, and as such we will talk about this research in light of two papers, the first topic came under the title (repetition and its effect on persuasion), while the second topic was called (intentionality of concentration and its effect) In persuasion.